Ca handling during Excitation-Contraction Coupling in Heart Failure - Zima, Aleksey V. (Pflugers Arch, 2014)
In the heart, coupling between excitation of the surface membrane and activation of contractile apparatus is mediated by Ca released from the sarcoplasmic reticulum (SR). Several components of Ca machinery are perfectly arranged within the SR network and the T-tubular system to generate a regular Ca cycling and thereby rhythmic beating activity of the heart. Among these components, ryanodine receptor (RyR) and SR Ca ATPase (SERCA) complexes play a particularly important role and their dysfunction largely underlies abnormal Ca homeostasis in diseased hearts such as in heart failure. The abnormalities in Ca regulation occur at practically all main steps of Ca cycling in the failing heart, including activation and termination of SR Ca release, diastolic SR Ca leak, and SR Ca uptake. The contributions of these different mechanisms to depressed contractile function and enhanced arrhythmogenesis may vary in different HF models. This brief review will therefore focus on modifications in RyR and SERCA structure that occur in the failing heart and how these molecular modifications affect SR Ca regulation and excitation-contraction coupling.